2008
DOI: 10.1152/ajplung.00391.2007
|View full text |Cite
|
Sign up to set email alerts
|

The ΔF508-CFTR mutation results in increased biofilm formation byPseudomonas aeruginosaby increasing iron availability

Abstract: Enhanced antibiotic resistance of Pseudomonas aeruginosa in the cystic fibrosis (CF) lung is thought to be due to the formation of biofilms. However, there is no information on the antibiotic resistance of P. aeruginosa biofilms grown on human airway epithelial cells or on the effects of airway cells on biofilm formation by P. aeruginosa. Thus we developed a coculture model and report that airway cells increase the resistance of P. aeruginosa to tobramycin (Tb) by >25-fold compared with P. aeruginosa grown on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
264
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(281 citation statements)
references
References 71 publications
(99 reference statements)
16
264
1
Order By: Relevance
“…More recently in a comprehensive study of iron in CF, Ghio et al (2013) demonstrated increased levels of iron and iron-related proteins in bronchoalveolar lavage fluids from CF children, in macrophages of explanted CF lungs and in lung tissue from CF patients -clear evidence of altered iron homeostasis and of iron accumulation in the CF airways (Ghio et al, 2013). Consistent with these findings, Moreau-Marquis et al (2008) demonstrated that airway cells expressing DF508-CFTR released more extracellular iron than cells rescued with WT-CFTR (Moreau-Marquis et al, 2008). Furthermore, iron and ferritin levels are positively correlated with c.f.u.…”
Section: Iron and Cfmentioning
confidence: 73%
See 1 more Smart Citation
“…More recently in a comprehensive study of iron in CF, Ghio et al (2013) demonstrated increased levels of iron and iron-related proteins in bronchoalveolar lavage fluids from CF children, in macrophages of explanted CF lungs and in lung tissue from CF patients -clear evidence of altered iron homeostasis and of iron accumulation in the CF airways (Ghio et al, 2013). Consistent with these findings, Moreau-Marquis et al (2008) demonstrated that airway cells expressing DF508-CFTR released more extracellular iron than cells rescued with WT-CFTR (Moreau-Marquis et al, 2008). Furthermore, iron and ferritin levels are positively correlated with c.f.u.…”
Section: Iron and Cfmentioning
confidence: 73%
“…Moreau-Marquis et al (2008) demonstrated reduced P. aeruginosa biofilm growth on epithelial cells treated with an iron chelator and subsequently demonstrated (Moreau-Marquis et al, 2009) tobramycin in combination with iron chelators can eliminate P. aeruginosa biofilms. In a recent study, the same group have shown that a combination of hypocyanite and lactoferrin enhances the ability of tobramycin and aztreonam to eliminate P. aeruginosa biofilms on lung epithelial cells (Moreau-Marquis et al, 2015).…”
Section: Novel Therapeutic Strategies Targeting Iron Acquisition In Cmentioning
confidence: 91%
“…In both the static and the flow cell assays, we found that the CFBE monolayer could withstand the presence of P. aeruginosa for up to 8 hours after inoculation without any sign of alteration. Epithelial monolayer integrity can be assessed by phase-contrast microscopy using an inverted microscope 1 ( Figure 1A) or by differential interference contrast (DIC) microscopy throughout the experiment 5 . Over time, P. aeruginosa will produce toxins and virulence factors which accumulate and can damage the epithelial cell monolayer fully or in sections ( Figure 1B-1C).…”
Section: Representative Resultsmentioning
confidence: 99%
“…Specifically, the Static Co-culture Biofilm Model and the Flow Cell Co-culture Biofilm Model take advantage of the ability of P. aeruginosa to interact with and bind to the epithelial surface of the lung. Using these models, we have shown that the response of the co-culture biofilms to antibiotic treatment is unique and that these models are more likely to accurately reflect the infectious state 1,5 . In this regard, we have reported that the resistance to tobramycin increases by >25-fold when P. aeruginosa biofilms are grown on airway cells compared to biofilms grown on abiotic surfaces such as glass 5 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation